PET Radioligands for imaging of the PDE10A in human: current status. (19th January 2019) - Boscutti, Giulia; A Rabiner, Eugenii; Plisson, Christophe
Highlights: Evaluation of 6 PET radioligands for PDE10 A imaging in human has been summarised. Suitable carbon-11 and fluorine-18 PET radioligands are available for in vivo quantification of the PDE10 A in human. PDE10 A PET imaging in patients may help define therapeutic indications of PDE10 A inhibitors. PDE10 A PET imaging supports the enzyme involvement in neurodegenerative disorders. Abstract: The development of β + emitter tracers labelled with carbon-11 or fluorine-18 having optimal characteristics of affinity and selectivity for the phosphodiesterase 10 A protein has received considerable attention, due to the major implication of this enzyme in neurological and psychiatric disorders, such as Hungtington's disease, Parkinson's disease and schizophrenia. The ability to quantify PDE10 A availability in the human brain in vivo will thus aid understanding its role in neurodegenerative and neuropsychiatric pathophysiology as well as providing a valuable tool for drug development. This manuscript reviews the different compound series assessed to date as PET radioligand for the PDE10 A in human and their use to support the development programmes of novel drugs or to evaluate PDE10 A alterations in pathologies as Huntington`s, Parkinson`s Diseases and Schizophrenia.